PEMANFAATAN ARANG AKTIF TEMPURUNG KELAPA SEBAGAI BIOSORBEN DALAM MENURUNKAN KADAR BESI (Fe) PADA AIR SUMUR GALI DIKELURAHAN LEMBO KEC.TALLO KOTA MAKASSAR - Sappewali Sappewali; Adim Adim; C. Selry Tanri; Sitti Aminah (KOLONI, 2023)
Inorganic and organic components, including various dangerous heavy metals such as iron (Fe), can cause water pollution, which is detrimental to the body of organisms because they are toxic. Biosorbent is one of the methods that can reduce the level of iron content in dug well water by using activated charcoal from coconut shells as a filter. This study aimed to determine the pH value, temperature and decrease in Fe levels in dug well water using coconut shell activated charcoal as a biosorbent with time variations of 7 (P1), 14 (P2) and 21 (P3) days. This research is quasi-experimental with a pre-and post-test design with two measurements. Data from laboratory examinations were processed and analyzed using descriptive statistical tests. The results showed that dug well water's pH, temperature, and iron (Fe) level before filtering were 8.71, 31.670C, and 1.87 ml/L. After filtering using active coconut shell charcoal media as a biosorbent, pH values varied from 8, 50 (P1), 8.32 (P2) and 7.69 (P3). The temperature values remain unchanged at 31 degrees with 31.560C (P1), 31.670C (P2) and 31.440C (P3). Levels of iron (Fe) showed a significant decrease from 1.82 mg/L (5%) in P1, 1.20 mg/l (67%) in P2 and 1.11 (76%) in P3. In conclusion, the iron (Fe) content decrease in dug well water has the highest value on the 21st day, with a 76% reduction.  Keywords: active charcoal, Biosorbent, Fe Level, dug well water, Tallo District, Makassar.